P-113 Biomarkers of dying in cancer patients; an exploration of the biology of dying. Issue Volume 7:Issue (2017)Supplement 2 (1st November 2017) - Coyle, Séamus; Reid, Victoria Louise; McDonald, Rachael; Nwosu, Amara Callistus; Mason, Stephen R; Probert, Chris; Ellershaw, John E
Abstract : Background: The Neuberger review made a number of recommendations to improve end of life care, including research into the biology of dying. An important aspect of the biology of dying is the identification of biomarkers as indices of disease processes. Biomarkers have the potential to inform the current, limited understanding of the dying process and assist clinicians in recognising dying, in particular how to distinguish dying from reversible acute deterioration. Objectives: To critically appraise the literature on biological factors that may be used as prognostic indicators in advanced cancer patients. Methods: A systematically structured review was conducted using three electronic databases. Studies reporting prognostic biomarkers in cancer patients with a median survival of ≤90 days. Results: 30 articles were included. Seven prognostic biological factors demonstrated Grade A evidence (lymphocyte count, white blood cell count, serum C-reactive protein, albumin, sodium, urea and alkaline phosphatase). An additional eleven prognostic factors were identified with Grade B evidence (platelet count, international normalised ratio, serum vitamin B12, prealbumin, bilirubin, cholesterol, aspartate aminotransferase, alanine transaminase, 40 lactate dehydrogenase, pseudocholinesterase and urate). A number of biomarkers were specifically identified in the last two weeks of life but limitations exist. Conclusions: The biology of dying is an important area for future research, with the evidence focused on signs, symptoms and prognostic factors. This review identifies a number of common themes shared amongst advanced cancer patients and highlights candidate biomarkers which may be indicative of a common biological process to dying.